Identifying Training Needs And Client Satisfaction Of Vocational Rehabilitation Services For Students With Physical, Intellectual, Or Multiple Disabilities In Kuwait - (M.J.) O. Al Fawair, Ahmad (2013)
Training needs and client satisfaction are two of the major concerns in vocational rehabilitation but has not yet been adequately addressed in Kuwait. The objectives related to training needs are to determine the psychometric characteristics of an adapted training needs inventory for the Kuwait context, explore demographic characteristics, compare and identify the training needs across different demographic characteristics, and identify the knowledge domains with the highest training need. The objectives related to client satisfaction are to determine the psychometric characteristics of a developed client satisfaction survey for the Kuwait context, explore demographic characteristics, compare client satisfaction and identify the client satisfaction across different demographic characteristics, identify the client satisfaction dimension that has the lowest satisfaction, and compare parent satisfaction and student satisfaction of vocational rehabilitation services. A survey methodology with sequential explanatory QUAN-qual research design was used. The samples of this study consisted of service providers (764), student (484), and parents (1170) in vocational rehabilitation schools in Kuwait. The results related to training needs revealed high internal consistency reliability for the inventory. Six distinct factors were extracted. Years of experience, job title category, and qualification predict training needs scores. Significant differences in training needs were obtained across age, experience, qualification, and job title.